Risk factors for cardiac rupture complicating myocardial infarction: a PRISMA meta-analysis and systematic review. (28th November 2018) - Hao, Wen; Lu, Shangxin; Guo, Ruifeng; Fan, Jingyao; Zhen, Lei; Nie, Shaoping
Abstract : Cardiac rupture (CR) is a complication of acute myocardial infarction (AMI) that is associated with a high mortality rate. This study aimed to identify the risk factors for CR in patients with AMI. Medline, Cochrane, EMBASE, and Google Scholar databases were searched for relevant literature published through September 16, 2018. Eligible studies included patients with AMI and compared factors between patients with and without CR. Sixteen studies were identified and included in the meta-analysis. Results revealed that female gender (pooled OR=2.72, 95% CI 2.04 to 3.63, p<0.001), older age (pooled difference in means=6.91, 95% CI 4.20 to 9.62, p<0.001), infarction at left anterior descending coronary artery (LAD) (pooled OR=1.85, 95% CI 1.03 to 3.32, p=0.039), and anterior wall infarction (pooled OR=1.87, 95% CI 1.30 to 2.68, p=0.001) were associated with increased risk of CR, whereas history of MI, smoking, and multivessel disease were associated with reduced risk of CR. Patients treated with primary percutaneous coronary intervention (PCI) had reduced risk of CR, while patients who had received any thrombolysis had increased risk of CR. In conclusion, results of systematic review and meta-analysis of existing literature suggest that risk factors for CR in patients with AMI include female gender, older age, new-onset MI, non-smoking status, LAD infarction, anterior wall infarction, and single-vessel disease. Furthermore, treatment with primary PCI may help reduce the risk for CR, while thrombolysis might increase the risk for CR.